Hubungan antara asupan energi, asupan lemak, dan obesitas pada remaja siswa-siswi SLTP di Kota Yogyakarta dan di Kabupaten Bantul - Ana Medawati; Hamam Hadi; I Dewa Putu Pramantara (Jurnal Gizi Klinik Indonesia, 2005)
Background: The prevalence of obesity in young children and adolescents has been increasing very dramatically during the last two decades, especially in big cities. High intake of energy and fat may have contributed to obesity.Objective: To examine the relationship between energy intake, fat intake and obesity among adolescents.Method: A Case Control Study was conducted in 2003. Subjects were Junior High School students, age 10–15 years, living in the city of Jogjakarta and Bantul Regency were included in the study. Data on  nutrition intake were collected by using Food Frequency Questionnaires from 140 obese and 140 non obese junior high school students.Results: On average, the energy intake among cases and controls from the city of Jogjakarta were 2818,32 ± 618,05 kcal/day and 2210,42 ± 329,81 kcal/day respectively. Whereas total average of energy intake among  cases and controls from Bantul were 2416,99 ± 673,52 kcal/day and 1778,09 ± 312,03 kcal/day respectively. Obesity was significantly associated (p < 0.05) with total energy and fat intakes in both city Jogjakarta and Bantul.Conclusion: Obesity was associated with total energy and fat intakes in Junior High School Students.